Sistem Informasi Pemesanan Kelompok Wisatawan Pada Green Valley Waterpark [PT.NAS] - Rindiani Tri Lestari; Muhamad Fatchan; Annisa Maulana Majid (Prosiding Sains dan Teknologi, 2022)
Green Valley Waterpark is one of the recreational areas in the city of Purwakarta. The construction of an online group ordering information system aims to help expand marketing and help staff find data easily. This website system was built using CodeIgniter 4. The research method used is waterfall. The test method used is BlackBox. The information system that has been built will provide information that has been inputted by the staff, such as rides, facilities, the latest activities. And can manage tourist data to tourist group booking data. In addition, the tourist group booking information system will also display a booking report that has been input based on staff needs. This information system makes it easy to get information for potential tourists who want to visit Green Valley Waterpark. Tourists can view activities, route information, rides and facilities available online, place an online order by logging in first in order to place an order. and staff can manage data - information data quickly and accurately. Keywords: Information Systems, Booking, Tourism, Waterfall, CodeIgniter 4